2005
DOI: 10.1097/00001888-200510001-00025
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Characteristics and Response Times for One-Best-Answer Questions in Relation to Number and Source of Options

Abstract: Use of smaller numbers of options (and more items) results in more efficient use of testing time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 10 publications
1
21
1
Order By: Relevance
“…In a recent study it was shown that difficulty increases as the number of options increases in a one-bestanswer question. (Swanson et al, 2005) Are our results contradictory to this finding? Perhaps they are contradictory, or perhaps we are observing that the nature of the problem changes when there are no options presented.…”
Section: The Effect Of Clinical Presentation On Reasoning Strategiescontrasting
confidence: 72%
See 1 more Smart Citation
“…In a recent study it was shown that difficulty increases as the number of options increases in a one-bestanswer question. (Swanson et al, 2005) Are our results contradictory to this finding? Perhaps they are contradictory, or perhaps we are observing that the nature of the problem changes when there are no options presented.…”
Section: The Effect Of Clinical Presentation On Reasoning Strategiescontrasting
confidence: 72%
“…The explanation as to why the EM format favours hypothetico-deductive reasoning is unclear, but we would propose the hypothesis that presenting a list of diagnostic options, of which one is definitely the correct answer, might facilitate a process of excluding all diagnoses except one; i.e., hypothetico-deductive reasoning. In support of this hypothesis is the observation that the time taken to answer a one-best-answer question increases as the number of options increases, (Swanson, Holtman, Clauser, & Sawhill, 2005) suggesting that if more diagnoses are offered, more diagnoses are considered. This finding has important implications for studies evaluating the effect of reasoning strategies on diagnostic success.…”
Section: Discussionmentioning
confidence: 98%
“…Items with a discrimination index below 0.30 are considered to be poor discriminators [5]. Some of our test items performed poorly in this respect, especially in the first PASAT run (Figure 2 panel A), although items with larger numbers of options are usually more discriminating that items with fewer options [21].…”
Section: Discussionmentioning
confidence: 99%
“…Students' assessment and evaluation are vital part of the teaching and learning process [4][5]. According to Swanson et al, [6][7] among the different types of students' learning achievements and progress the multiple-choice questions are globally the most utilized.…”
Section: Item Analysismentioning
confidence: 99%